Assembly line productivity improvement as re-engineered by MOST - Karim, A.N. Mustafizul; Tuan, Saravanan Tanjong; Emrul Kays, H.M. (Emerald Group Publishing Ltd., 2016)
The purpose of this paper is to address and solve operational problems of an automotive industry in reaching production target by adopting Maynard Operation Sequence Technique (MOST) as lean and productivity improvement strategies. Design/methodology/approach: In the undertaken case of auto-car rear window assembly line, a recurring production shortfall in fulfilling the daily demand is seemingly due to inappropriate work method. Initial observation of the operations led to suspect certain lapses in initiatives to adopt the time standards, to reduce or eliminate non-value added motions, to design suitable aisle and to assign tasks among workstations in a balanced manner. Subsequently an attempt is made to pinpoint the causes of poor performance and the bottlenecks through process flow analysis and time study by applying MOST. The elemental tasks are closely examined for possible reduction of workstation times by choosing efficient work methods with ergonomic features. Thus appropriate hand tools, jigs and fixture with nominal investment are prescribed to incorporate in the assembly works. The operational changes as steered by the MOST application have enhanced the workflow with a shorter cycle time which led to a substantial increase in productivity. Findings: The productivity of the assembly line is increased by more than 29 percent from the earlier capacity through the MOST application which is deemed to meet the current level of demand. Originality/value: The adopted framework for recognizing the effectiveness of MOST to expose and rectify the flaws in work methods without much investment is expected to be beneficial for a manufacturer in securing the competitiveness.